2022
DOI: 10.3390/foods11233786
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Bread Supplemented with Agaricus bisporus Powder: Effect on Bioactive Substances Content and Technological Quality

Abstract: Supplementation of food products with mushroom powder increases their health-promoting value, but at the same time affects technological quality, which often play a key role for consumers. The aim of the research was to determine the effect of adding freeze-dried white and brown button mushrooms (2.5% and 5%) to wheat bread on its health-promoting properties such as antioxidant activity (DPPH, FRAP), total polyphenols and vitamin D2 content and as well as the technological quality as colour and texture. The br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 74 publications
3
12
0
Order By: Relevance
“…This finding is in support of the study by ref which also found that cellulose addition in bread slightly increased the Δ E value with no effect on the overall acceptability of bread in sensory evaluation. A similar result was also obtained by previous authors when white bread flour was supplemented with brown mushroom powder …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is in support of the study by ref which also found that cellulose addition in bread slightly increased the Δ E value with no effect on the overall acceptability of bread in sensory evaluation. A similar result was also obtained by previous authors when white bread flour was supplemented with brown mushroom powder …”
Section: Resultssupporting
confidence: 91%
“…The addition of cellulose in bread as a result of the specific volume reduction mainly relates to gluten dilution and the decrease of final volume during proofing . The presence of SAP extract in MCC as an antioxidant dietary fiber might have affected the activity of the yeast and production of CO 2 , thus causing a reduction in loaf volume. , A similar trend in bread volume was observed in other studies, where herb (Cistus incanus L.) was used to fortify wheat bread …”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Texture profile analysis (TPA) parameters were determined using a Brookfield Texturometer (model CT34500, serial 8555940, Middleboro, MA, USA) and Brookfield Engineering Labs Inc.’s TexturePro CT V1.4 Build 17 software. The test conditions were: TA25/100 compression plate probe, double compression, speed 0.5 mm/s, deformation 40%, load cell 4.5 kg, evaluating hardness, cohesiveness, elasticity, adhesiveness, resilience, fracturability, and chewiness [ 47 ]. The samples were measured in their entirety (42–45 mm in diameter, with a height of 15–20 mm in thickness), taking the measurements as quickly as possible to avoid moisture loss.…”
Section: Methodsmentioning
confidence: 99%
“…Another important aspect is that additives with a high content of bioactive compounds should be used in products that are willingly and frequently consumed [10].…”
Section: Introductionmentioning
confidence: 99%